On the meaning of “plasticity” in neuroscience and mental health research and its relation to the action of psychedelic therapy - R. L. Carhart-Harris; R. J. Zeifman; L. Pasquini; B. Nandi; C. Rohani-Shukla; S. Suseelan; P. Mediano; F. Rosas; C. Timmermann; H. Kettner; P. A. McConnell (Frontiers in Neuroscience, 2026)
First-line dictionary definitions of “plasticity” describe it as the ability (of a thing) to be shaped or molded; we call this “plasticity proper” (PP). In neuroscience, however, “neural plasticity” or “neuroplasticity” is defined as an induced change in brain function or structure. These two plasticities are not the same. Several popular biomarkers of neuroplasticity index part of an evoked process, often linked to learning. Paradoxically, these processes often bias phenotypic canalization, the opposite of phenotypic plasticity. Recognizing this paradox puts into question the custom of using “plasticity” as a shorthand for all neuroplastic phenomena. This custom risks an overgeneralization fallacy and the conflation of assays of evoked brain changes with plasticity proper. We also question extrapolating from any biomarker of neuroplasticity to improved mental health, whether it be aligned with plasticity proper or not. The relationship between the two is, logically, context dependent . As a resolution, we propose a new construct, “mediational and recalibrative plasticity” (MR-P) and show how markers of it can describe and predict examples of phenotypic plasticity, where those phenotypes are states and traits relevant to mental health. In contrast to many markers of neuroplasticity, MR-P is aligned with plasticity proper.